Fiqh Wakaf Progresif: Wakaf Tunai (Cash Waqf) di Indonesia dalam Memberdayakan Ekonomi Umat Berbasis Maqâshid Ibn ‘Asyur - Moh. Mujibur Rohman Rohman (IAIN Langsa, 2022)
This research is a normative research which is part of library research or (library research). Where this research will examine cash waqf which is not far from the existing problem formulation. Namely; 1) how is the concept of cash waqf in Indonesia and how is it related to the concept of madzhab fiqf?; 2) what is the role of the state in the success of cash waqf and progress in building the economy of the people in the future?; last 3) what is the maqashid of cash waqf as an economic empowerment of the people in the perspective of maqashid Ibn 'Asyur?. The results of the study show that the concept of Indonesian waqf fiqh allows cash waqf or cash waqf. This permissibility was responded to by the emergence of the MUI fatwa on cash waqf, and accompanied by several laws and regulations such as the Waqf Law no. 41 of 2004 as well as several other regulations. Not only that, the progress of cash waqf in the future is expected to help the people's economy, such as empowering MSMEs, agriculture, commerce, livestock and other economic sectors of the people. With the maqashidy-based analysis Ibn 'Asyur shows that there are two maqashids to be addressed in the practice of cash waqf itself. First, maqashid ammah in the form of general benefit (universal) for economic empowerment of the people which can be allocated to places of worship, education, health and other social matters. Second, Maqashid Khassah in the form of hifz al-mâl makes waqf objects more productive. Keywords: Cash Waqf, People's Economy, Maqâshid Ibn 'Asyur